2021
DOI: 10.1177/10664807211052480
|View full text |Cite
|
Sign up to set email alerts
|

Familism and Parenting Stress in Latinx Caregivers of Young Children with Developmental Delays

Abstract: Several studies have documented the difficult experience of raising a child with a developmental delay (DD; DeGrace et al., 2014) but the majority of research has focused on non-Latinx White families and their experiences in childrearing and interacting with service providers (Hayes & Watson, 2013; Blanche et al., 2015). Additionally, stigma associated with mental illness and DD disproportionally affects Latinx communities (Burke et al., 2019). Familism plays a unique role among families of Latinx backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In the studies of some Hispanic parents of children with mental disorders with a low intensity of familism, a strong correlation was observed between the parent's affiliate stigmatization and experiencing parental stress. The obtained result confirms the fact that familism can act as a buffer protecting the parents of children with mental disorders (Martin et al, 2022).…”
Section: Family Valuessupporting
confidence: 79%
“…In the studies of some Hispanic parents of children with mental disorders with a low intensity of familism, a strong correlation was observed between the parent's affiliate stigmatization and experiencing parental stress. The obtained result confirms the fact that familism can act as a buffer protecting the parents of children with mental disorders (Martin et al, 2022).…”
Section: Family Valuessupporting
confidence: 79%
“…In valuing and attending to the positive features of parents’ routine events and interactions, the positive valence of daily parenting hassles may increase, thereby undermining Latino parents’ stress. Second, Latinos’ cultural valuation of familism (Campos & Kim, 2017; Martin et al, 2021) may contribute to greater familial support, a primary buffer of parenting stress that may further attenuate the perceived intensity of daily parenting hassles. Third, religious values within Latino cultural groups may drive the commonly held belief in “God's plan” or in the notion that having a child with a disability or developmental delay is a challenge sent directly from God, thereby tempering one's negative appraisals of parenting hassles (Skinner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Parents' collectivistic values and perceived discrimination has been found to predict higher parental familismo , which in turn has been found to predict higher levels of positive parenting practices (Lorenzo‐Blanco et al, 2016). For example, prior research has found possible links between familismo and lower levels of parenting stress in Latinx families with children who have a developmental delay (Martin, Marin, McIntyre, & Neece, 2021). Considering the importance of these values and the unique concerns within the immigrant Latinx community, we utilized a theoretical framework that included these values.…”
Section: Acculturation Levelsmentioning
confidence: 99%